Pedunculated Osteochondroma of the Right Foot Following Traumatic Injury: A Rare Case Report - Al Hakim, Muhammad Fariz; Pandelima, Maksum (Jurnal Health Sains, 2025)
Osteochondromas are the most common benign bone tumors, accounting for 20-50% of all benign osseous neoplasms. However, osteochondromas involving the foot and ankle are rare, representing only 3-10% of all cases. The relationship between trauma and osteochondroma development remains a subject of clinical interest. A 37-year-old female presented with three-month history of progressive right foot pain following a traumatic fall down stairs. Examination revealed a 5cm × 5cm × 2cm firm, non-mobile mass on the lateral foot with restricted ankle motion. The mass had enlarged from 2cm × 2cm to 4cm × 4cm over three months. Pedunculated osteochondroma was diagnosed clinically and radiologically. Complete surgical excision was performed using osteoclasis technique. Histopathology confirmed benign osteochondroma with uneventful post-operative recovery. The temporal relationship between the traumatic fall and subsequent identification of the osteochondroma raises important questions about whether trauma triggered secondary osteochondroma development or simply brought attention to a pre-existing asymptomatic lesion. Post-traumatic osteochondromas are thought to arise from displacement of growth plate cartilage fragments through the cortex, though the exact mechanism remains incompletely understood. The progressive enlargement over three months in a skeletally mature adult was potentially concerning for malignant transformation; however, the clinical presentation and benign histopathological diagnosis confirmed a benign lesion. Plain radiography demonstrating cortical and medullary continuity with the parent bone remains the primary diagnostic modality, with cross-sectional imaging reserved for cases with atypical features or concern for malignancy. Osteochondroma should be considered in the differential diagnosis of post-traumatic foot masses presenting with hard swelling and restricted motion. Complete surgical excision achieves excellent outcomes with low recurrence rates. Timely diagnosis through appropriate imaging and multidisciplinary collaboration are crucial for optimal management.